2015
DOI: 10.1097/nmd.0000000000000295
|View full text |Cite
|
Sign up to set email alerts
|

Ten-Year Outcomes of First-Episode Psychoses in the MRC ÆSOP-10 Study

Abstract: Supplemental digital content is available in the article.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
71
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 97 publications
(77 citation statements)
references
References 43 publications
5
71
1
Order By: Relevance
“…63 64 65 Our results differ from previous long term follow-up studies of SEI treatment where participants seem to relapse after end of the intervention treatment. But we did not find an effect of prolonged treatment on our primary outcome, and therefore the results of the main trial outcomes cannot serve as a basis for recommending SEI treatment for five years.…”
Section: Discussioncontrasting
confidence: 99%
“…63 64 65 Our results differ from previous long term follow-up studies of SEI treatment where participants seem to relapse after end of the intervention treatment. But we did not find an effect of prolonged treatment on our primary outcome, and therefore the results of the main trial outcomes cannot serve as a basis for recommending SEI treatment for five years.…”
Section: Discussioncontrasting
confidence: 99%
“…Nonetheless, it has been shown that it is possible to reliably quantify the course of disorder using routine data from clinical notes (Bebbington et al, 2006). Moreover, our thorough approach to data extraction from clinical notes has ensured that the rates of remission and time to first remission reported in this study are consistent with earlier studies which collected data from face-to-face interviews only (Revier et al, 2015), extracted it retrospectively from clinical notes (Ajnakina et al, 2017;Bromet et al, 2005;Harrison et al, 2001;Kohler et al, 2009) or employed both approaches (Morgan et al, 2014;Schoeler et al, 2017). Many diagnostic categories assigned to patients on first contact with mental health services may either be provisional or likely to change over the illness course (Schwartz et al, 2000), as seen in our sample with a relatively high number of patients with a diagnosis of schizophreniform disorder.…”
Section: Limitationssupporting
confidence: 78%
“…A significant number of people with SMI can experience a reduction of both symptoms and associated impairments over time and make a full recovery. Research suggests that remission and recovery rates in first episode psychosis may be more favourable than previously thought, suggesting that a progressive deteriorating course of illness is not typical 3,4 . Indeed, for those who continue to live with the symptoms of psychosis, recovery in terms of personal, social and occupational aspirations is a realistic goal and sets the context for the recovery approach.…”
Section: What Is Severe Mental Illness?mentioning
confidence: 77%